Social Work in heart transplantation program: a social assessment - Silva, Ana Lucia da (2011)
Purpose: The aim of this study was to identify social, economic, cultural and environmental conditions that influenced the life and health of candidates for the transplantation program to provide subsidies to the multidisciplinary team. Methods: It was a quantitative, descriptive and retrospective study performed from January 2006 to December 2009 at the Heart Institute through structured interviews with sampling of 526 patients and their families. Results: The profile of patients was characterized by 67% of male predominance with 34% concentration of 51 to 60 years old patients; as to the school level, 50% corresponded to elementary school, 55% catholic; as to the marital status: 67% had spouse, 78% had caretakers, 54% were originated in the State of São Paulo, 54% used public transportation, 72% had their own home, 92% of domiciles had infrastructure and basic sanitation, 68% received social security benefits or assistance, 37% had per capita income of 1 to 2 minimum wages, 97% were linked to SUS. From the total social assessments carried out, 46% had social conditions for the proper monitoring of the program, 47% remained assisted by Social Workers to monitor social and family conditions subject to change, and 7% of patients presented hindering against their inclusion on the list. Conclusion: The social assessment is a prognostic tool to measure social life conditions of each individual, in order to identify socioeconomic and cultural factors in the daily routine of patients and their families that can facilitate, interfere or obstruct in their adhesion process, social reintegration and quality of life.